In-silico virtual screening for identification of potent inhibitor for L2-β-lactamase from Stenotrophomonas maltophilia through molecular docking, molecular dynamics analysis study. Issue 18 (12th December 2021) - Sharma, Ridhi; Jade, Dhananjay; Mohan, Surender; Chandel, Rahul; Sugumar, Shobana
Abstract: Stenotrophomonas maltophilia, a Multiple-Drug-Resistant proteobacterium found in healthy normal flora and fauna with an aerobic and non-fermentative respiratory process, is majorly involved in Healthcare-Associated Infections (HAI). The Multiple-Drug-Resistance takes place by secretion of the β-Lactamase enzyme, which hydrolyzes the β-Lactam antibiotics and currently serving as a significant clinical challenge by substantially effecting the mortality rate. In this study, involved 2D Similarity, Molecular docking, and Molecular Simulation for the commercially available ZINC database compounds to overcome this resistance mechanism and find out a proper potent inhibitor for the target L2-β-Lactamase, which would not get cleaved by the hydrolytic activity of the L2-β-Lactamase natural enzyme. The ZINC35053014 compound had the highest binding energy: −8.51Kcal/mol with hydrophobic interaction at THR235 and formation of hydrogen bonds at SER70, SER130, ASN170, LYS234, THR235, SER237, and ARG244. In total, 08 hit compounds subjected for the stability check of the protein-ligand complex (MD simulation) analysis which, concluded in the same RMSD, RMSF, and Rg values at the comparison between known compounds and the selected virtual hit compounds. These selected virtual hit compounds can be experimentally verified and used as lead compounds for the future search of β-Lactamase potent inhibitors for S. maltophilia . Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001